The Significance of Oxidative Stress in Articular Cartilage Ageing and Degradation - Henrotin, Yves; Blanco, Francisco J.; Aigner, Thomas; Kurz, Bodo (Current Rheumatology Reviews, 2007)
It is well recognised that age is a primary risk factor for the development of osteoarthritis (OA), but the mechanisms by which ageing contributes to an increased susceptibility to OA are poorly understood. Reactive oxygen species seem to play a key role in this process by acting on cellular and extracellular levels. According to the redox status of the biological medium, they can be regulators or dysregulators of the mitochondrial and cell signalling machinery. Further, ROS induce structural and functional alteration of the extracellular matrix, leading to matrix stiffness and brittleness. This paper is an extensive review of the literature about the oxidative-related cartilage changes during the ageing process. It highlights the possible relationships between ageing, chronic inflammation and cartilage degradation in OA.
Keywords: Cartilage